Analisis Penanggulangan Bencana Banjir oleh Badan Penanggulangan Bencana Daerah Kota Bekasi (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2020)
This study aims to identify and analyze flood management carried by the Bekasi City Disaster Management Agency (BPBD). This study used qualitative research methods. Data collection techniques are carried out through interviews, observation and documentation. While the validity data used was source triangulation, and data analysis model was carried out through data reduction, data presentation, and conclusions. The results showed that the pre-disaster stage mitigation measures were carried out installing an early warning system in five locations of the Cikeas-Cileungsi River flow, then training task force members and finally disseminating early warning to the people of Bekasi City so far it has well. However socialization disaster response not been carried out thoroughly the flood victims in Bekasi City who have been affected by the floods. Then the time of disaster, BPBD could not evacuate flood victims maximally and thoroughly to flood victims in Bekasi City. Post-disaster phase, rehabilitation activities are carried out cleaning up garbage and mud at flooded points and carrying out psychological rehabilitation flood victims. Meanwhile, reconstruction activities were carried out calculating loss of damaged buildings and then reporting it to Public Works Office for follow-up. However, post-disaster coordination between BPBD and community has not well. So the rehabilitation and reconstruction process has not been evenly distributed to all flood victims in Bekasi City. Based on this explanation, can be concluded that, implementation of flood disaster management by Bekasi City BPBD has not well and various obstacles and problems are still being found.